Supramolecular structure of racemic 5-hydroxy-4-(4-methoxyphenyl)-10-oxa-4-azatricyclo[5.2.1.02,6]dec-8-en-3-one - Goekce, Aytas Guerhan; Celik, Cumali; Ayguen, Muhittin; Ocal, Nuket; Bueyuekguengoer, Orhan (INT UNION CRYSTALLOGRAPHY, 2008)
The structure of the title compound, C15H15NO4, comprises a racemic mixture of chiral molecules containing five stereogenic centres. The cyclohexane ring tends towards a boat conformation and the two tetrahydrofuran rings adopt envelope conformations. Molecules are linked into sheets parallel to ( 100) by a combination of O-H center dot center dot center dot O, C-H center dot center dot center dot O and C-H center dot center dot center dot pi hydrogen bonds, leading to a two-dimensional supramolecular structure.
Keywords: Chemistry; Crystallography